Effect of seed processing treatments on oil quality of Ethiopian sesame varieties. Issue 1 (31st December 2023) - Neme, Kumera; Tola, Yetenayet B.; Mohammed, Ali; Tadesse, Eneyew; Shaheen, Farzana; Ahmed, Shakil; Jahan, Humera; Qaiser, Shama; Müller, Felicitas
ABSTRACT: In Ethiopia, sesame is number one oilseed crop in terms of export value, but with low value addition practice. This research aimed to determine effect of varieties and pre-oil extraction treatments on yield and quality of the oil. Results showed that yield varied from 47.1 to 57.5% with iodine value (IV) from 106 to 113 g/100 g, free fatty acid (FFA) 0.47 to 1.36%, and peroxide value (PV) of 0.66 to 7.04 meq O2/kg. Palmitic, oleic and linoleic acid were the major fatty acids in the oil and characterized by high unsaturated (80–85%) and less saturated (15–20%) fatty acids. All pre-oil extraction treatments increased the oil content, with minor effects on color, FFA, and PV as compared to the oil from the raw seed. However, roasting enabled to extract better oil yield with low PV and less constitutes of FFA.